2014
DOI: 10.1111/aji.12209
|View full text |Cite
|
Sign up to set email alerts
|

Research Gaps in Defining the Biological Link between HIV Risk and Hormonal Contraception

Abstract: Epidemiologic data suggest an association between depot medroxyprogesterone acetate (DMPA), a progesterone-based hormonal contraceptive, and increased risk of HIV acquisition and transmission. DMPA is highly effective and is among the most commonly used form of hormonal contraception in areas of high HIV prevalence. Thus, defining the biological mechanisms that contribute to the potential negative synergy between DMPA and HIV is key and may facilitate the identification of alternative contraceptive strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 68 publications
1
42
0
Order By: Relevance
“…Several biological mechanisms may underlie an association between DMPA and increased risk of HIV acquisition in women, including: structural changes and alterations in the permeability of the female genital tract, alterations of the frequency and activity of cellular targets for infection, modulation of levels of soluble mediators and defense molecules in the genital tract, alteration of innate and adaptive immune responses, and changes in the female genital tract microbiome [27, 28]. Research in this area has been stymied by lack of identified biomarkers that would predict significant risk of future HIV acquisition.…”
Section: Dmpa-im and Hiv Risk In Womenmentioning
confidence: 99%
“…Several biological mechanisms may underlie an association between DMPA and increased risk of HIV acquisition in women, including: structural changes and alterations in the permeability of the female genital tract, alterations of the frequency and activity of cellular targets for infection, modulation of levels of soluble mediators and defense molecules in the genital tract, alteration of innate and adaptive immune responses, and changes in the female genital tract microbiome [27, 28]. Research in this area has been stymied by lack of identified biomarkers that would predict significant risk of future HIV acquisition.…”
Section: Dmpa-im and Hiv Risk In Womenmentioning
confidence: 99%
“…It has been suggested that hormonal contraceptives may affect human immunodeficiency virus (HIV) susceptibility within the vaginal vault by modulating the genital immune system, regulating genital epithelial cells, inducing cervical ectopy, and affecting the local microflora [2][3][4][5][6]. Data regarding vaginal epithelial thickness differences between hormonal contraceptive users and nonusers are however indecisive, and the clinical relevance of some of these limited changes is unclear [7][8][9][10][11][12]. Thus, the global impact of the biological effects of hormonal contraceptives needs to be explored in detail to understand how they may affect susceptibility to HIV acquisition and transmission.…”
Section: Introductionmentioning
confidence: 99%
“…This adds to the growing amount of evidence of the biological effect of progestins on the immune system and on the immune environment in lower FRT 7,13,14 . However, it remains to be established whether the contraceptive-mediated alterations to systemic and genital immune mechanisms described here and in other studies exert an effect on the susceptibility to HIV-1 and other infections.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies have sought to understand the biological mechanisms underlying the effect of hormonal contraception on HIV-1 acquisition (reviewed in 7,13,14 ). Hormonal contraception use has been linked to changes in the frequencies of immune cells in genital mucosae [15][16][17][18][19][20][21] and altered levels of cytokines, chemokines, and antiviral factors in cervicovaginal fluid 22,23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation